2019
DOI: 10.14207/ejsd.2019.v8n5p9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Industrial Waste to Produce Ceramic Coatings on Metal

Abstract: Industrial processes are activities that produce large amounts of wastes. Often these wastes are disposed in dam or landfills, occupying large areas and causing environmental damage such as the contamination of water and soil. According to the Circular Economy concept, waste should be minimized and reused as raw material in a new process. This work describes two residues, namely red mud (bauxite residue) and waste foundry sand (WFS), whose chemical compositions indicate their suitability for use as protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This principle also highlights reusing everything possible in a production process and recycling what cannot be used anymore. 1 Following the circular economy concept, Antunes et al 2 emphasize the importance of cost minimization and sustainable manufacturing. Those authors also say that converting foundry sand (FS) into something else is a good example of it, as FS is a waste generated in aluminum production in Brazil, and it ends up reducing the lifespan of landfills.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This principle also highlights reusing everything possible in a production process and recycling what cannot be used anymore. 1 Following the circular economy concept, Antunes et al 2 emphasize the importance of cost minimization and sustainable manufacturing. Those authors also say that converting foundry sand (FS) into something else is a good example of it, as FS is a waste generated in aluminum production in Brazil, and it ends up reducing the lifespan of landfills.…”
mentioning
confidence: 99%
“…4 Foundry Sand (FS) has been studied for environmental applications due to its iron content, varying from 2% to 23% in weight. 2,5 Antunes et al, 2 for example, demonstrated that FS can be used in the coating of aluminum alloys by plasma electrolytic oxidation. According to those authors, the hydrophobic ceramic coating generated by FS is highly adherent to the alloy and they are also chemically/thermally stable, according to the XRD signals indicating the formation of γ-alumina and iron of the formed coating.…”
mentioning
confidence: 99%